Knowledge and Attitude of Brazilian Elementary School Teachers Towards Dental Trauma - Daniela Coelho de Lima; Suzely Adas Saliba; Cléa Adas Saliba Garbin; Leandro Araujo Fernandes; Leopoldo Cosme-Silva; Nemre Adas Saliba (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate both knowledge and attitude of public elementary school teachers in Alfenas, Minas Gerais, Brazil, towards Traumatic Dental Injuries (TDIs). Material and Methods: Four hundred and seventy-one teachers from 10 schools were invited to participate in the research. Two hundred and twelve were accepted, being randomly selected to answer semi-structured questionnaires. Statistical tests Chi-Square and Fisher's Exact Test were also used for the other variables at a significance level of 5% (p<0.05). Results: 212 teachers answered; 34% had first-aid training in college or even voluntarily (22.6%), but only 7.1% had taken training about TDIs. Only 7.5% were satisfied with the knowledge about TDIs, and 12.3% felt prepared to face it. About 10.8% had seen any type of TDI; 53.3% would report to the headmaster and 8% to the school dentist in a TDI event. The teachers' first attitude towards TDIs would be contacting the child's parents (63.2% and 58.5%, respectively). About 47.2% would handle the tooth properly (by the crown). Nearly 90.1% would carry out a permanent tooth dental reimplant, which would be conducted immediately (71.2%). About 36.3% of the teachers storage the avulsed tooth in a liquid: milk (46.7%) and saline solution (24.7%). The dry media mentioned were paper (18.9%) and gauze or cotton (15.1%). Most of the teachers (96.2%) stated that they would like to receive information on TDI. Conclusion: Elementary school teachers in Alfenas have partial knowledge about traumatic dental injuries.